Tindak Tutur Direktif dalam Konten Mic Check TLID pada Kanal Youtube Team Liquid ID - Aditya Javits Saputra; Asep Purwo Yudi Utomo (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study was motivated by the dominant use of directive speech acts in competitive esports communication. The purpose of this study is to describe the types, functions, and effects of directive speech acts in mic check content on the Team Liquid ID YouTube channel. This study uses a qualitative descriptive approach. The research subject is mic check content on the Team Liquid ID YouTube channel. The object of this study is directive speech acts. Data collection methods include observation using basic recording techniques and advanced techniques such as the Free-Form Conversation Observation Technique (SLBC) and note-taking. The results of this study identified the form of directive speech acts, namely direct literal speech acts. The functions of directive speech acts identified include command, request, invitation, advice, and prohibition. Furthermore, regarding the effects of using directive speech acts in the study, three positive effects were found, such as the encouraging effect, the effect of hoping to follow, and the relieving effect.